2017
DOI: 10.1016/j.trsl.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Mesencephalic astrocyte-derived neurotrophic factor (MANF), a new player in endoplasmic reticulum diseases: structure, biology, and therapeutic roles

Abstract: Mesencephalic astrocyte-derived neurotrophic factor (MANF), a newly identified 18 kDa soluble protein, localizes to the luminal endoplasmic reticulum (ER). ER stress can stimulate MANF expression and secretion. In Drosophila and zebrafish, MANF regulates dopaminergic neuron development. In contrast, in mice, MANF deficiency leads to diabetes and activation of the unfolded protein response. Recent studies in rodent models have demonstrated that MANF mitigates diabetes, exerts neurotrophic function in neurodegen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 64 publications
(111 reference statements)
1
24
0
Order By: Relevance
“…A large number of studies have suggested that MANF expression can be up-regulated to exert its neuroprotective effects in response to a variety of neurological insults. ER stress can also enhance the expression of MANF, which protects cells from the unfolded protein response (UPR) induced apoptosis [9,49]. In our study, a western blot analysis revealed that the level of MANF began to rise at 3 h and peaked at 24 h after t-SCI, Double immunofluorescence staining confirmed that the expression of MANF increased in neurons after t-SCI.…”
Section: The Neuroprotective Functions Of Manfsupporting
confidence: 59%
“…A large number of studies have suggested that MANF expression can be up-regulated to exert its neuroprotective effects in response to a variety of neurological insults. ER stress can also enhance the expression of MANF, which protects cells from the unfolded protein response (UPR) induced apoptosis [9,49]. In our study, a western blot analysis revealed that the level of MANF began to rise at 3 h and peaked at 24 h after t-SCI, Double immunofluorescence staining confirmed that the expression of MANF increased in neurons after t-SCI.…”
Section: The Neuroprotective Functions Of Manfsupporting
confidence: 59%
“…Apostoloua et al (2) reported that ER stress can initiate UPR, which, in turn, activates adaptive and apoptotic pathways, and the 2 pathways have different roles in disease prognosis. MANF, as a UPR modulator, inhibits cell proliferation and ER-induced cell death (2,41). MANF is predominantly expressed in neurons and only slightly expressed in microglia and astrocytes (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…However, humans excrete approximately 25% of the total absorbed TCC in urine. Furthermore, in renal tubular cells, ER dysfunction induces tubular injury and apoptosis and plays a pathogenic role in the onset and progression of renal tubulo‐interstitial disease, which ultimately advances to end‐stage renal disease . According to WISH, hspa5 and hsp90b1 were both enhanced in intrinsically expressing sites, head, pharyngeal region, pectoral fin bud, and intestinal tract after exposure to 10 μg/L TCC for 16 hours.…”
Section: Discussionmentioning
confidence: 99%